Complete acid-based hydrolysis assay for carbohydrate quantification in seaweed: a species-specific optimized approach - Kostas, Emily Tsambika; Wilkinson, Stuart; White, Daniel A.; Cook, David J. (Springer Verlag, 2017)
Accurate quantification of the carbohydrate content of biomass is crucial for many bio-refining processes. The most commonly followed protocol is typically a modification of the NREL-based assay (specifically designed for carbohydrate analysis from lignocellulosic biomass). However, this NREL protocol was revealed to be excessively thermochemically harsh for seaweed biomass. This can result in erroneously low total sugar quantification as the reaction severity can degrade a proportion of the liberated sugars to decomposition products such as furans. Here we describe an optimization of the total acid hydrolysis protocol for accurate quantification of the carbohydrate content of seaweeds. Different species of seaweed can be accurately evaluated for their carbohydrate contents by following this optimized method.